Synthesis of some heterocyclic compounds based on (2, 3-dioxo-2, 3-dihydro-1H-indol-1-yl) acetyl acetic acid derivatives - Selim, Nahed Mohamed; Arief, Mohammed Helmy; Ahmed, Mohammed H (International Journal of Basic and Applied Sciences, 2013)
Reactions of isatin–N–acetylchloride 2 with equivalent amount of hydrazine hydrate gave 2-(2, 3-dioxo-2, 3-dihydro-1H-indol-1-yl) acetohydrazide 3 which was then cyclized to give [1, 2, 4] triazino [4, 3-a] indole-3, 10 (2H, 4H)-dione 5 but when 2 reacted with excess of hydrazine hydrate it give 2[(2, 3-bishydrazono)-2, 3-dihydro-1H-indol-1-yl] acetohydrazide 4. Isothiocyanate derivative 6 was prepared from the corresponding acid chloride and ammonium thiocyanate in acetone. The reactions of isothiocyanate with anthranilic acid, glycine, benzoyl glycine, hydrazine hydrate and benzoyl hydrazine were also investigated. The condensation reaction of benzoyl glycine with isothiocyanate in the presence of benzaldehyde gave 16 which was easily cyclized to give 17.